2020
DOI: 10.3390/nu12041014
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol Form of Omega-3s Improves Its Bioavailability in Humans Compared to Other Forms

Abstract: Numerous benefits are attributed to omega-3 fatty acids (OM3) especially in cardiovascular health. However, bioavailability and clinical efficacy depend on numerous factors, including OM3 form, food matrix effects (especially the lipid content of the diet), and metabolic capacity. Here, we show in humans that a "pre-digested" OM3-sn-1(3)-monoacylglycerol lipid structure (OM3-MAG) has a significantly greater absorption at high therapeutic doses (2.9 g/day) than the most commonly OM3-ethyl ester (3.1 g/day) form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Monoacylglycerols can act as protectors against digestive actions, carrying omega 3 fatty acids and then modify their bioavailability Cuenoud et al. [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Monoacylglycerols can act as protectors against digestive actions, carrying omega 3 fatty acids and then modify their bioavailability Cuenoud et al. [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although most dietary lipids in foods were constituted of TAGs, however, TAGs are required to be hydrolyzed into free fatty acids and sn‐2‐ MAG by lipolytic enzymes, mainly sn‐1,3 specific pancreatic lipases in the upper part of the gastrointestinal tract in the digest process (Yen & Farese, 2003), whereas Monoacylglycerols (MAGs) are lipase independent and considered as being in a predigested form. Recent studies have found that MAG containing EPA/DHA exhibits a high degree of efficient absorption, especially under impaired absorption conditions compared to conventional dietary TAG (Caroline et al., 2018; Cuenoud et al., 2020). Therefore, n‐3 PUFA in the MAG predigested form may offer a clinical advantage to patients struggling with lipid malabsorption/maldigestion problems.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, PUFA contained in MAG and DAG are highly bioavailable (Meynier and Genot, 2017). On this basis, GLA‐ and SDA‐based MAG may offer a clinical advantage to patients struggling with fat malabsorption/maldigestion problems, for instance, patients with cystic fibrosis (Cuenoud et al, 2020). On the other hand, n ‐3 PUFA are better protected against oxidation when they are included in polar lipids, while the bioavailability of n ‐3 PUFA is higher when included in the PL fraction than in that of the TAG (Jiménez Callejón et al, 2020).…”
Section: Resultsmentioning
confidence: 99%